2018
DOI: 10.21873/invivo.11231
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Exercise Training on Breast Cancer

Abstract: Abstract. Background Breast cancer is still a major medical, social and economic problem due to the increasing prevalence and unsatisfactory treatment results. In 2013, nearly 235,000 new cases of breast cancer were reported in the United States, which accounted for 29% of all malignant neoplasms and was related to 14% risk of death. Based on current trends, over 23 million of new cases will be diagnosed by the year 2030 (1).Numerous scientific reports indicate the impact of physical activity on the developmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Among the included studies, 21 studies ( Steiner et al, 2013 ; Shalamzari et al, 2014 ; Alvarado et al, 2017 ; Alizadeh et al, 2018 ; Murphy et al, 2011 ; Aveseh et al, 2015 ; Leila et al, 2015 ; Malicka et al, 2015 ; Isanejad et al, 2016 ; Cui, 2017 ; Nasiri et al, 2017 ; Lyv Di et al, 2021 ; Qi et al, 2013 ; Siewierska et al, 2018 ; Siewierska et al, 2020 ; Wen et al, 2010 ; Gholamian et al, 2020 ; Vulczak et al, 2020 ; Wennerberg et al, 2020 ) reported that exercise could decrease the tumor volume, 1 ( Faustino-Rocha et al, 2016 ) reported negative effects of exercise, and 2 ( Smeda et al, 2017 ; Garritson et al, 2019 ) reported that exercise had no effect on the tumor volume.…”
Section: Resultsmentioning
confidence: 99%
“…Among the included studies, 21 studies ( Steiner et al, 2013 ; Shalamzari et al, 2014 ; Alvarado et al, 2017 ; Alizadeh et al, 2018 ; Murphy et al, 2011 ; Aveseh et al, 2015 ; Leila et al, 2015 ; Malicka et al, 2015 ; Isanejad et al, 2016 ; Cui, 2017 ; Nasiri et al, 2017 ; Lyv Di et al, 2021 ; Qi et al, 2013 ; Siewierska et al, 2018 ; Siewierska et al, 2020 ; Wen et al, 2010 ; Gholamian et al, 2020 ; Vulczak et al, 2020 ; Wennerberg et al, 2020 ) reported that exercise could decrease the tumor volume, 1 ( Faustino-Rocha et al, 2016 ) reported negative effects of exercise, and 2 ( Smeda et al, 2017 ; Garritson et al, 2019 ) reported that exercise had no effect on the tumor volume.…”
Section: Resultsmentioning
confidence: 99%
“…The aim of our project entitled "Impact of Physical Training on the Carcinogenesis and Progression of Rat Mammary Glands" was the assessment of the impact of physical training on the course of cancer, depending on the intensity of exercise training and the examined prevention model. The results related to primary prevention were presented by Malicka et al (13), whereas initial results related to secondary prevention were presented by Siewierska et al (14). In the present article, we report the assessment of the influence of physical activity on sex hormone levels (estradiol and progesterone) and the expression of their receptors (ER, PR), as well as the level of apoptosis of tumor cells in the model of secondary prevention.…”
mentioning
confidence: 75%
“…Tissue collection. Six months following MNU administration, the animals were sacrificed (13,14). All tumors in the animals that were detected on palpation were collected and measured.…”
Section: Methodsmentioning
confidence: 99%
“…Obesity, systemic metabolism, and patient fitness are emerging as influencing factors for cancer free-survival as both preemptive measures and post-operative disease progression. [16][17][18] Obesity causes a state of chronic lowgrade inflammation, where soluble factors, such as cytokines, chemokines, and growth factors are systemically modulated. This has been shown to give rise to immunosuppressive populations, notably MDSCs, as compensatory mechanisms to counteract obesity-associated diseases.…”
Section: Discussionmentioning
confidence: 99%